HADQAT AL-‘ARIFIN» AND ITS MANUSCRIPTS - О.О. Туякбaев; Е., Мевлут (Journal of Oriental Studies, 2019)
In the academic scientific environment, year by year, the number of fundamental studies of the history and theory of the mystical religion of Islam Sufism is increasing. Recently, Chagatai religious works have attracted a lot of attention of researchers, as the primary source on the his tory of formation and the peculiarities of «Popular Islam» in Central Asia. One of interest Chagatay works to researchers is «Khadiqat al‘arifin» (end of the XIVth century). It was written by a prominent representative of the Yasawi Sufik school Ishaq Khoja ibn Isma’il Ata alQazygurti alTurkistany. This article provides a brief overview of the manuscripts of this work, preserved in foreign funds. Key words: Hagiography, Sufism, Yasawi, Manuscript, Codicology, Chagatai language.